Juridic Review Filling Membership of the Regional Representative Board of the Republic of Indonesia Post the Decision of the Constitutional Court Number 30/PUU-XIV/2018 - Fadjrin Wira Perdana (Budapest International Research and Critics University, 2021)
Positions as functionaries of Political Parties with DPD membership are not common before the 2019 General Election as a political practice that is prohibited by Law Number 7 of 2017 concerning General Elections jo. KPU Regulation Number 21 of 2018. However, with the Constitutional Court Decision Number 30/PUU-XVI/2018 jo. KPU Regulation Number 26 of 2018 states that concurrent positions of political party functionaries in the DPD membership are a violation of the law, so all parties should obey it. In this study, analysis and discussion of the legal aspects of the dual position practice will be carried out after the Constitutional Court's Decision.